FORMATION OF PUBLIC ADMINISTRATION MECHANISMS IN THE SPHERE OF SOCIAL SECURITY OF UKRAINE AT THE PRESENT STAGE - Serheieva , Ludmila; Sobchenko , Valentyna (Theory and Practice of Public Administration, 2019)
The topicality of the present research is stipulated by the aggravating negative trends in the social sphere, which are taking place at the present stage of development of the state and society, in particular: a rapid deterioration in the living standards, backdated wages, low pension rates, property differentiation of the population, aloofness of the majority of the population from social life, narrowed access to education, healthcare and culture, low level of social support for the poor people, etc., which threatens social security that is an integral part of the national security. Despite a large number of scientific works in the said field, there are still understudied issues of forming mechanisms for the public administration of social security both in general, and in a specific historical period. The paper objective lies in determining the specific features of social security at the present stage of state development and their impact on forming the public administration mechanisms to ensure it.Based on the conducted research, the specific features of social security at the present stage of development of the state and society have been identified. Taking into account the obtained research results, we can make conclusions as follows.The mechanisms for public administration of social security derive from the methods of public administration of the social sphere, which can be divided into several kinds according to their classification attributes, in particular by their forms of influence and ways of implementation.The main functions of public administration of social security include: regulatory, supporting; organizational, coordination, social, direct administration of social sector components, and controlling.Thus, it can be stated that the process of forming the mechanism for public administration of social security at the present stage is influenced by: – special features of social security in a specific historical period; – imperfection of the legal framework in effect, which regulates relations in the social sphere;– complexity and multi-aspect nature of the category of ‘social security’;– ineffectiveness of government institutions’ performance of their tasks and functions laid upon them by the Constitution and the laws of Ukraine; – the character and scale of external and internal threats and challenges to both social security and the national security as a whole, etc. Therefore, a proper standard of social security is provided by the activity of public administration subjects that are entrusted by the state with the function of ensuring it through a system of coordinated mechanisms, adequate to counteract external and internal threats of the current period of time. Without this policy, it is impossible to achieve economic recovery, launch the mechanism of administering the socio-economic situation in Ukraine, and create effective mechanisms for social protection of the population as part of social security.A promising area of further research in the said field should be substantiation of the theoretical and methodological basis for forming a complex mechanism for public administration of social security.